Initial starting dose of inhaled corticosteroids in adults with asthma: a systematic review. Issue 12 (24th November 2004) - Powell, H; Gibson, P G
Abstract : Background: Asthma guidelines vary in their recommendations for the initial dose of inhaled corticosteroid (ICS) in asthma. A systematic review of the literature was conducted to establish the optimal starting dose of ICS for asthma in adults. Methods: Randomised controlled trials comparing two doses of the same ICS in adults with asthma and no concomitant inhaled or oral corticosteroid were assessed. Included trials were analysed according to the following ICS dose comparisons: high (⩾800 μg/day beclomethasone (BDP)) versus moderate (400<800 μg/day BDP) (n = 7); moderate versus low (<400 μg/day BDP) (n = 6); step down versus constant dose (n = 4). Results: Fourteen publications describing 13 trials were included in the review. Studies (n = 4) that compared a step down approach with a constant moderate/low dose of ICS found no difference in lung function, symptoms, or rescue medications between the two treatment approaches (p>0.05). There was no difference in the change in morning peak flow after treatment with high compared with moderate dose ICS. When compared with low dose ICS, moderate dose ICS significantly improved morning peak flow (change from baseline WMD 11.14 l/min, 95% CI 1.34 to 20.93) and nocturnal symptoms (SMD −0.29, 95% CI −0.53 to −0.06). Conclusions: For patients with asthma who require ICS, starting with a moderate dose is equivalent to starting with a high dose and stepping down. The small non-significant benefits of starting with a high ICS dose are not of sufficient clinical benefit to warrant its use. Initial moderate ICS doses appear to be more effective than an initial low ICS dose.